Functional and Structural Analysis of HrcA Repressor Protein from Caulobacter crescentus - Michelle F. Susin; Humberto R. Perez; Regina L. Baldini; Suely Lopes Gomes (2004)
A large number of bacteria regulate chaperone gene expression during heat shock by the HrcA-CIRCE system, in which the DNA element called CIRCE serves as binding site for the repressor protein HrcA under nonstress conditions. In Caulobacter crescentus, the groESL operon presents a dual type of control. Heat shock induction is controlled by a sigma32-dependent promoter and the HrcA-CIRCE system plays a role in regulation of groESL expression under physiological temperatures. To study the activity of HrcA in vitro, we purified a histidine-tagged version of the protein, and specific binding to the CIRCE element was obtained by gel shift assays. The amount of retarded DNA increased significantly in the presence of GroES/GroEL, suggesting that the GroE chaperonin machine modulates HrcA activity. Further evidence of this modulation was obtained using lacZ transcription fusions with the groESL regulatory region in C. crescentus cells, producing different amounts of GroES/GroEL. In addition, we identified the putative DNA-binding domain of HrcA through extensive protein sequence comparison and constructed various HrcA mutant proteins containing single amino acid substitutions in or near this region. In vitro and in vivo experiments with these mutated proteins indicated several amino acids important for repressor activity.